2014
DOI: 10.1016/j.jmii.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia bloodstream infection: Comparison between community-onset and hospital-acquired infections

Abstract: Community-onset S. maltophilia infection deserves attention. Patients with community-onset SMBSI have reduced disease severity and lower mortality rate when compared to HA SMBSI. Underlying structural/mechanical abnormalities, especially those caused by malignancies, are common in SMBSI cases and should be investigated when bacteremia occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 29 publications
2
63
4
Order By: Relevance
“…40 Recent studies, however, reported that the TMPeSXT susceptibility of S. maltophilia in southern Taiwan was only 68.9%. 24 In agreement with these most recent results, we found that 69.6% of our isolates were susceptible to TMPeSXT. Based on recent antimicrobial susceptibility results of blood isolates of S. maltophilia and the results reported here, 24 we suggest that clinicians in Taiwan should use TMPeSXT as empirical therapy with caution for patients when S. maltophilia infections were suspected, because of high frequency of TMPeSXT resistance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…40 Recent studies, however, reported that the TMPeSXT susceptibility of S. maltophilia in southern Taiwan was only 68.9%. 24 In agreement with these most recent results, we found that 69.6% of our isolates were susceptible to TMPeSXT. Based on recent antimicrobial susceptibility results of blood isolates of S. maltophilia and the results reported here, 24 we suggest that clinicians in Taiwan should use TMPeSXT as empirical therapy with caution for patients when S. maltophilia infections were suspected, because of high frequency of TMPeSXT resistance.…”
Section: Discussionsupporting
confidence: 93%
“…24 In agreement with these most recent results, we found that 69.6% of our isolates were susceptible to TMPeSXT. Based on recent antimicrobial susceptibility results of blood isolates of S. maltophilia and the results reported here, 24 we suggest that clinicians in Taiwan should use TMPeSXT as empirical therapy with caution for patients when S. maltophilia infections were suspected, because of high frequency of TMPeSXT resistance. Continued surveillance and additional research should focus on potentially effective alternatives to TMPeSXT for the treatment of S. maltophilia infections.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in our study, nearly 50% of sul -positive S. maltophilia strains were non-susceptible to moxifloxacin and levofloxacin. Moreover, it has been reported that the overuse of fluoroquinolones worldwide has resulted in a higher resistance rate among many pathogenic bacteria, including S. maltophilia (Chang et al, 2014; Pien et al, 2015). Therefore, it would be prudent to use them as initial empirical antibiotics for sul -positive strains.…”
Section: Discussionmentioning
confidence: 99%
“…(4,(13)(14)(15). Stenotrophomonas maltophilia bacteremia was reported as 21% -51% (8,(16)(17)(18)(19)(20). Lai et al (21) found that while S. maltophilia bacteremia originating from respiratory tract was associated with higher mortality, CVC-related bacteremia was inversely associated with mortality.…”
Section: Discussionmentioning
confidence: 99%